AI and Human Rights: Navigating Ethical and Legal Challenges in Developing Nations - Patrick Chukwunonso Aloamaka; Moses Ogorugba Omozue (UIN Sunan Gunung Djati, 2024)
The swift progress of artificial intelligence (AI) offers substantial opportunities and significant challenges, particularly concerning human rights in developing nations. This article explores the legal issues and moral conundrums brought about by AI technology's increasing influence on sectors such as healthcare, education, and governance. In developing nations, AI deployment often occurs without robust legal frameworks, potentially infringing on privacy, autonomy, and equity. This study employs a doctrinal research methodology to analyse the effects of AI on fundamental human rights, using case studies to illustrate both benefits and risks. It examines the role of international human rights standards and local legal systems in mitigating adverse impacts. The results highlight the complex interplay between technological innovation and human rights protection, proposing practical recommendations for policymakers, technologists, and legal practitioners. Ultimately, the goal is to foster an environment where AI can contribute to sustainable development while upholding the dignity and rights of all individuals in developing countries. This research contributes to the scientific understanding of AI's ethical and legal implications in the context of human rights.